Pengembangan Ekonomi Kreatif Kerajinan Sutera di Kabupaten Wajo - Helda Ibrahim; Suardi Bakri; Awaluddin Yunus; Tamzil Ibrahim (Universitas Negeri Makassar, 2019)
Silk development in Wajo Regency is relatively strategic since it involves farmers, opens businessopportunities, gives an opportunity for populist economic development, and increases farmer’s income and foreignexchange. Wajo Regency is known as silk producer city in South Sulawesi. Silk weaving activity has been the dailyactivity of Sengkang Bugis people since their ancestors. The research purposes were (1) to what extent is thecharacteristic of silk craftsmen in silk craft development conducted in Tanasitolo Sub-district Wajo Regency; and(2) how is silk product development in Tanasitolo Sub-district Wajo Regency. The research was conducted atPakkana Village Tanasitolo Sub-district Wajo Regency with consideration that the area is one of centers for silkproduct business development in Wajo Regency. Samples taken were 30 people using purposive sampling. Theresearch results indicate that the characteristics of silk craftsmen in Tanah Sitolo area of Wajo Regency were: 1)Respondents in Pakkanna Village were all female; (2) the highest respondent age (80%) was between 26-50 yearsold; 13.33% were under 25 years old and 6.67% were above 50 years old; (3) respondent’s family dependents weremostly 5-6 people, which was 36.67 percent; (4) based on experience, most respondents has the longest experiencesof 20-25 years, which was 13 percent; and (5) most respondents (50%) had average level of education of junior highschool (SMP). Silk craft development had been long conducted but it was in the level of design motive renewalpacked with modern motive according to merchants’ order level and consumers’ direct order. The development hasbeen a creative economic-based development.